PREVALENCE OF THE SUBTYPES OF OBSESSIVECOMPULSIVE DISORDER AMONG DIAGNOSED PATIENTS IN THE KURDISTAN REGION IN IRAQ - Faraj, Saman Anwar (Journal of Sulaimani Medical College, 2025)
Background The clinical manifestation of obsessive-compulsive disorder (OCD) differs from patient to patient, indicating that the content of the obsessions and compulsions varies. Therefore, the present study aims to find the prevalence of the sub-types of OCD. Objectives This study addresses the association of the sub-types of obsessions and compulsion with gender, age, and marital status. Patients and Methods Seventy-five patients with OCD from a psychiatric clinic, who were diagnosed through an unstructured interview, participated in this study, which utilized a retrospective research design. The data was obtained from the case files of the patients, where their diagnosis and the content of their obsessions and compulsion were specified. Results The results showed that the most prevalent obsession in the sample was contamination obsessions. They were followed by religious, doubting, aggressive, symmetry, and sexual obsessions. As for compulsions, cleaning/ washing was the most common among the participants, followed by mental rituals, whereas checking and arranging compulsions were the least common. The results also revealed that contamination obsession had a significant association with gender. Conclusion Similar results regarding cleaning/washing compulsions showed a significant association with gender.
Keywords: OCD; obsession; compulsion; clinical sample; Kurdistan Region Iraq